Beginning JavaScript the ultimate guide to modern JavaScript development - Ferguson, Russ (Apress, 2019)
Introduction to JavaScript -- JavaScript and development tools -- JavaScript variables -- JavaScript objects and arrays -- JavaScript functions and context -- JavaScript and events -- JavaScript and programming paradigms -- JavaScript and debugging -- JavaScript and client-side development -- JavaScript and server-side development -- JavaScript and application frameworks : Angular -- JavaScript and application frameworks : React -- JavaScript and static deployment